A Growth-Promoting Bacteria, Paenibacillus yonginensis DCY84T Enhanced Salt Stress Tolerance by Activating Defense-Related Systems in Panax ginseng - Sukweenadhi, Johan; Balusamy, Sri R.; Kim, Yeon-Ju; Lee, Choong H.; Kim, Yu-Jin; Koh, Sung C.; Yang, Deok C. (Frontiers in Plant Science, 2018)
Panax ginseng (C.A. Mayer) is a well-known medicinal plant used in traditional medicine in Korea that experiences serious salinity stress related to weather changes or incorrect fertilizer application. In ginseng, the use of Paenibacillus yonginensis DCY84T to improve salt stress tolerance has not been thoroughly explored. Therefore, we studied the role of P. yonginensis DCY84T under short-term and long-term salinity stress conditions in a controlled environment. In vitro testing of DCY84T revealed high indole acetic acid (IAA) production, siderophore formation, phosphate solubilization and anti-bacterial activity. We determined that ten-minute dip in 1010 CFU/ml DCY84T was sufficient to protect ginseng against short-term salinity stress (osmotic stress) upon exposure to 300 mM NaCl treatment by enhancing nutrient availability, synthesizing hydrolyzing enzymes and inducing osmolyte production. Upon exposure to salinity stress (oxidative and ionic stress), strain DCY84T-primed ginseng seedlings were protected by the induction of defense-related systems such as ion transport, ROS scavenging enzymes, proline content, total sugars, and ABA biosynthetic genes, as well as genes involved in root hair formation. Additionally, ginseng primed with DCY84T and exposed to 300 mM NaCl showed the same metabolite profile as control ginseng plants, suggesting that DCY84T effectively reduced salt stress. These results indicated that DCY84T can be widely used as a microbial inoculant to protect ginseng plants against salinity stress conditions.